Effect of Nitriding on the Microstructure and Mechanical Properties of Stainless Steels - Faltejsek, Petr; Joska, Zdenek; Pokorny, Zdenek; Dobrocky, David; Studeny, Zbynek (Manufacturing Technology Journal, 2019)
Austenitic stainless steels are common spread in many industries. Plasma nitriding is one of the few technologies that allows surface modification of austenitic stainless steels. In this study, a plasma nitriding method to form a hard surface layer at two different austenitic steels AISI 302 and AISI 316L. The surface morphology, chemical composition and mechanical properties of the formed layers were described and the results were compared with each other. The formed nitrided layers on both steels created a uniform multi-phase layer which was characterized by high hardness and very good abrasion resistance.
Keywords: austenitic stainless steel; plasma nitriding; microhardness; metallography